New insights on the Paleoproterozoic Basement of Tandilia Belt, Río de La Plata Craton, Argentina: First HF isotope studies on zircon crystals - Cingolani, Carlos Alberto (2010)
New insights on the Paleoproterozoic Basement of Tandilia, Río de la Plata Craton, Argentina: First Hf isotope studies in zircon crystals.